Mutation analysis of p53 gene in cervical cancer and useful polymorphic variants in exons 3 and 4 (2021)
Background: Factors contributing to the pathogenesis and progression of cervical cancer include poor attitude to screening and health intervention, late presentation, among others. Mutations in p53 gene have been attributed to several cancer cases. The present study was designed to find relationships between the mutation patterns in p53 gene and cervical carcinoma staging. Such knowledge could contribute to early diagnosis of cervical cancer. Results: From the sequence analysis of p53 gene fragment isolated by polymerase chain reactions (PCR), nineteen (19) polymorphic variants were identified. Missense mutations occurred in 47% of the samples, 32% were silent mutations, 16% were frameshift mutations and 5% nonsense mutations. Socio-biological characteristics of the study participants revealed that 60% have husbands with multiple sexual partners and that only 23.3% of the participants have ever had the Papanicolaou (Pap) smear test prior to diagnosis, whilst 20% were unaware of the screening test. Conclusions: Increased severity of cervical carcinoma staging as revealed from the histopathological analysis was found to be associated with accumulation of higher levels of mutations in the p53 gene. Molecular analysis of p53 gene mutations may prove useful as a screening biomarker for cervical cancer.